PERSEPSI PENDENGAR GEN-Z KOTA PALEMBANG PADA IKLAN DI RADIO GLOBAL 101 FM - Feiza Salsabila Deka; Intan Putri; Annisa Ghina Istighfarany; Andriadi Anugrah Ilahi (Berajah Journal, 2026)
This study aims to analyze the perception of Generation Z (Gen-Z) listeners in Palembang City toward advertisements on Radio Global 101 FM amid the shifting patterns of media consumption in the digital era. As a conventional communication medium, radio faces significant challenges in maintaining its relevance in a landscape dominated by visual and interactive digital platforms. This research employed a qualitative approach using thematic analysis (Braun & Clarke, 2019). Data were collected through in-depth interviews with Gen-Z informants aged 18–25 years who are active listeners of Radio Global 101 FM. The findings reveal that Gen-Z’s perception of radio advertising is ambivalent. While they appreciate the uniqueness of audio elements—such as jingles, announcer intonation, and sound effects—that foster emotional connection, many consider radio ads less relevant to their digital lifestyles. The analysis identifies three key patterns: (1) the strength of audio as radio’s core identity, (2) a communication gap between conventional advertising formats and young audiences’ expectations, and (3) the importance of message relevance and emotional engagement in enhancing advertising effectiveness. This study concludes that the success of radio advertising among Gen-Z depends on creative, authentic, and contextually relevant audio content. Radio Global 101 FM is encouraged to innovate through storytelling, humor, and cross-platform collaborations to remain engaging and competitive.